Further Defining the Role of the Laboratory Genetic Counselor. Issue 4 (20th February 2016) - Waltman, Lindsey; Runke, Cassandra; Balcom, Jessica; Riley, Jacquelyn D.; Lilley, Margaret; Christian, Susan; Zetzsche, Lindsay; Goodenberger, McKinsey L.
Abstract: Laboratory genetic counseling is becoming increasingly common as a result of increased laboratory services and genetic testing menus, as well as growing job responsibilities. Christian et al. (2012 ) provided the first quantitative data regarding the roles of the laboratory‐based genetic counselor (LBGC) finding that two of the most prevalent roles are as customer liaisons and communicators of test results. The goal of the present study was to further delineate the role of the LBGC by addressing specific tasks that LBGCs are involved with on a day‐to‐day basis. A survey was designed to expand upon themes identified in the Christian et al. (2012 ) study by querying specific tasks performed in several categories of potential LBGC job duties. An invitation for LBGCs to participate was distributed via email to the membership of the National Society of Genetic Counselors (NSGC) and the Canadian Association of Genetic Counsellors (CAGC). We identified 121 genetic counselors who primarily work in the laboratory setting or whose job role includes a laboratory component. Almost all respondents performed customer liaison/case coordination (95 %), and interpretation and result reporting (88 %). The most frequently performed tasks within these categories involved addressing questions from clients, making phone calls with genetic testing results, obtaining clinical or family history information for results interpretation, and composing case‐specific interpretations for unique results and/or obtaining literature references to support interpretations. The study results also point to trends of expanding roles in sales and marketing, variant interpretation and management responsibilities. Results of this study may be useful to further define the full scope of practice of LBGCs, aid in the development of new LBGC positions and expand current positions to include roles related to test development, research, and student supervision. It may also aid in curriculum updates for training programs to increase exposure to LBGC roles.